2003
DOI: 10.1128/aem.69.12.7224-7235.2003
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities Associated with GeologicalHorizons in Coastal Subseafloor Sediments from the Sea ofOkhotsk

Abstract: Microbial communities from a subseafloor sediment core from the southwestern Sea of Okhotsk were evaluated by performing both cultivation-dependent and cultivation-independent (molecular) analyses. The core, which extended 58.1 m below the seafloor, was composed of pelagic clays with several volcanic ash layers containing fine pumice grains. Direct cell counting and quantitative PCR analysis of archaeal and bacterial 16S rRNA gene fragments indicated that the bacterial populations in the ash layers were approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
411
3
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 425 publications
(448 citation statements)
references
References 40 publications
27
411
3
4
Order By: Relevance
“…The porous sponge mimics the porous layers (ash and sand layers) of the subseafloor sediments. Inagaki et al, (2003) and Kobayashi et al, (2008) reported that cultivable microbial components were generally more numerous in the porous layers than in the pelagic clay layers. In addition, the distinguishing feature of the DHS reactor is that the sponges are not submerged and freely placed in the atmosphere (Uemura and Harada, 2010).…”
mentioning
confidence: 99%
“…The porous sponge mimics the porous layers (ash and sand layers) of the subseafloor sediments. Inagaki et al, (2003) and Kobayashi et al, (2008) reported that cultivable microbial components were generally more numerous in the porous layers than in the pelagic clay layers. In addition, the distinguishing feature of the DHS reactor is that the sponges are not submerged and freely placed in the atmosphere (Uemura and Harada, 2010).…”
mentioning
confidence: 99%
“…E-mail : hyunjh@hanyang.ac.kr ํ–‰๋˜์–ด์™”๋‹ค (Gray and Herwig 1996;Ravenschlag et al 1999). ๊ทธ๋Ÿฌ๋‚˜ ์ตœ๊ทผ ๋ถ„์ž์ƒํƒœ๊ธฐ์ˆ ์˜ ๋ฐœ๋‹ฌ์„ ํ†ตํ•˜์—ฌ ์ œํ•œ๋œ ํ™˜๊ฒฝ์—์„œ๋งŒ ์„œ์‹ํ•œ๋‹ค๊ณ  ์•Œ๋ ค์ ธ ์žˆ๋˜ ๊ณ ์„ธ๊ท ์ด ์ผ๋ฐ˜ ํ•ด์–‘ ํ™˜๊ฒฝ ๋ฐ ์‹ฌํ•ด ํ‡ด์ ๋ฌผ (Vetriani et al 1999;Reed et al 2002;Inagaki et al 2003;Newberry et al 2004;Biddle et al 2006;Inagaki et al 2006), ๋‚จ๊ทน ํ‡ด์ ๋ฌผ (Bowman and McCuaig 2003;Kendall et al 2007), ๋ƒ‰์šฉ์ˆ˜(cold seep)์ง€์—ญ (Knittel et al 2005;Arakawa et al 2006), ๋ฉ”ํƒ„ ๋ˆ„์ถœ(methane seep)์ง€์—ญ (Lloyd et al 2006;Dang et al 2009), ํ•ด์ € ์—ด์ˆ˜๊ตฌ(hydrothermal vent)์ง€์—ญ (Takai and Horikoshi 1999;Reysenbach et al 2000;Teske et al 2002), ๋นˆ์˜์–‘(organic-poor)ํ•ด์—ญ (Sรธrensen et al 2004), ๊ฐฏ ๋ฒŒ(tidal flat) (Wilms et al 2006) ๋ฐ ์—ผ์Šต์ง€(salt marsh) (Nelson et al 2009)์™€ ๊ฐ™์€ ๋‹ค์–‘ํ•œ ํ•ด์–‘ํ™˜๊ฒฝ์—์„œ ๊ด‘๋ฒ”์œ„ ํ•˜๊ฒŒ ๋ถ„ํฌํ•˜๊ณ  ์žˆ์Œ์ด ๋ฐํ˜€์กŒ์œผ๋ฉฐ, ์ด๋ฅผ ๋ฐ”ํƒ•์œผ๋กœ, ๊ณ ์„ธ๊ท  ๋„ ์ง„์ •์„ธ๊ท ๊ณผ ๋งˆ์ฐฌ๊ฐ€์ง€๋กœ ํ•ด์–‘ ํ‡ด์ ๋ฌผ์—์„œ ์ƒ์ง€ํ™”ํ•™์  ๋ฌผ์งˆ์ˆœํ™˜์— ์ค‘์š”ํ•œ ์—ญํ• ์„ ๋‹ด๋‹นํ•˜๋Š” ๊ฒƒ์œผ๋กœ ์ธ์‹๋˜๊ณ  ์žˆ ๋‹ค (Knittel et al 2005;Biddle et al 2006;Hallam et al 2006;Nicol and Schleper 2006).…”
Section: ์„œ ๋ก unclassified
“…์™ธ๊ตญ์˜ ๊ฒฝ์šฐ ๋‹ค์–‘ํ•œ ํ•ด์–‘ ํ™˜๊ฒฝ์—์„œ ๋ฏธ์ƒ๋ฌผ์— ์˜ํ•œ ๋ฌผ์งˆ ์ˆœํ™˜์— ๋Œ€ํ•œ ์—ฐ๊ตฌ์™€ ํ•จ๊ป˜ 16S rRNA ์œ ์ „์ž ๋ถ„์„์„ ํ†ตํ•˜ ์—ฌ ํ•ด์–‘ ์ €์ธต ํ‡ด์ ๋ฌผ์—์„œ ๊ณ ์„ธ๊ท  ๊ตฐ์ง‘ ๋‹ค์–‘์„ฑ์— ๊ด€ํ•œ ์—ฐ ๊ตฌ๊ฐ€ ํ™œ๋ฐœํ•˜๊ฒŒ ์ง„ํ–‰๋˜๊ณ  ์žˆ๋‹ค (Vetriani et al 1999;Reed et al 2002;Inagaki et al 2003;Newberry et al 2004;Biddle et al 2006;Inagaki et al 2006). ์ด์— ๋น„ํ•ด, ๊ตญ๋‚ด ์—์„œ๋Š” ์ฃผ๋กœ ์—ฐ์•ˆ์ด๋‚˜ ๊ฐฏ๋ฒŒ์—์„œ ์ง„์ •์„ธ๊ท ์˜ ๋‹ค์–‘์„ฑ์— ๋Œ€ ํ•œ ์—ฐ๊ตฌ๊ฐ€ ๋‹ค์ˆ˜ ์ง„ํ–‰๋˜์—ˆ์œผ๋‚˜, ๊ณ ์„ธ๊ท ์— ๋Œ€ํ•œ ์—ฐ๊ตฌ๋Š” ๊ฐฏ๋ฒŒ ๊ณผ ๋™ํ•ด ์—ฐ์•ˆ์˜ ์ˆ˜์‹ฌ 500-650 m ์ •๋„์˜ ํ‡ด์ ๋ฌผ์—์„œ ์•”๋ชจ ๋‹ˆ์•„ ์‚ฐํ™”์™€ ๊ด€๋ จํ•œ ์—ฐ๊ตฌ์— ๋ถˆ๊ณผํ•œ ์‹ค์ •์ด๋‹ค (์ด ๋“ฑ 2001;์กฐ ๋“ฑ 2004;Kim et al 2005;Park et al 2008).…”
Section: ์„œ ๋ก unclassified
See 2 more Smart Citations